PROGRAM LINGKAR BACA CERIA SEBAGAI UPAYA PENINGKATAN KEMAMPUAN MEMBACA AWAL SISWA SEKOLAH DASAR - Parsyllah Minallah, Ninda; Rahman Hakim, Arif; Habibuddin; Nadiatul Soleha, Ria; Ulya, Manzilatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early reading difficulty among lower-grade elementary school students, such as letter recognition and reading fluency, remains a pivotal challenge in primary education. This study aims to describe the efforts to develop students' early reading skills at SD Negeri 6 Selong through the "Lingkar Baca Ceria" program. Using a descriptive qualitative method, data were gathered through structured observations and in-depth interviews with PPG pre-service teachers, lower-grade students, and the school principal. Data analysis was conducted through data reduction, data display, and drawing conclusions. The results indicate that the "Lingkar Baca Ceria" program effectively improves early reading skills by incorporating small-group reading strategies based on the Teaching at the Right Level (TaRL) approach. Students demonstrated significant progress in recognizing alphabets, blending syllables, and verbal fluency. Key supporting factors include the systematic utilization of concrete media (letter cards and illustrated storybooks) and the strategic role of pre-service teachers as adaptive learning facilitators. While field implementation faced challenges such as time constraints and a lack of reading material variations, the program successfully fostered students' reading confidence and collaborative learning. This study concludes that the "Lingkar Baca Ceria" program serves as an interactive and highly scalable alternative strategy for basic literacy enforcement in lower grades of elementary schools.